Assessment of performance in speed skating using IMUs - Leemreize, A. J. (University of Twente, 2024)
Speed skating performance is influenced by biomechanical factors, such as the stroke frequency, knee flexion angle, trunk angle, push-off angle and push-off force. It is not possible to capture these parameters with traditional motion capture systems all over a 400-m ice rink. This thesis evaluates the potential of inertial measurement units (IMUs) in measuring performance-related parameters in speed skating. Movella DOT sensors were used to measure kinematic data from speed skaters on an indoor ice rink. An algorithm was developed to estimate performance-related parameters, and the results were validated against the MVN Link system. The DOT sensors successfully detected the number of strokes and provided strong correlations with the MVN system for the push-off and knee flexion angles. However, trunk angle estimation showed significant inaccuracies, likely due to sensor placement. This study demonstrates the feasibility of using DOT sensors for kinematic analysis in speed skating. Future research is needed to improve the calibration protocol, validate the results of the DOT sensors against video analysis and explore the potential for real-time feedback.